Associations of emotional burden and coping strategies with sick leave among healthcare professionals: A longitudinal observational study. (March 2021) - Cheval, Boris; Mongin, Denis; Cullati, Stéphane; Uribe, Adriana; Pihl-Thingvad, Jesper; Chopard, Pierre; Courvoisier, Delphine S.
Abstract: Objectives: To investigate 1) whether care-related regrets (regret intensity, number of recent regrets) are associated with sick leave, independently of personality traits, perceived safety climate, and physical activity; and 2) whether these associations were mediated or moderated by coping strategies. Methods: Using a longitudinal international observational study (ICARUS), data were collected by the means of a weekly web survey. Descriptive and generalized estimation equations were performed. Results: A total of 276 newly practicing healthcare professionals (nurses, physicians, others) from 11 countries were included in this study. The average proportion of weeks with at least one day of sick leave was 3.2%. Nurses' sick leave increased with number of care-related regrets (Relative Risk [RR]=1.52; 95% Confidence Interval [CI]=[1.18; 1.95], p =.001), while physicians' sick leave increased with intensity of care-related regret (RR=1.21; 95%CI=[1.00; 1.21], p =.049). Coping was associated with lower risk of sick leave for nurses (RR problem-focused strategies = 0.53; 95%CI=[0.37; 0.74], p =.001, and RRphysical activity =0.68; 95%CI:[0.54; 0.85], p <.001), but not for physicians. Nevertheless, the association of regret with sick leave remained significant even when adjusting for coping. Finally, this study did not find evidence of moderation by the coping strategies. Conclusion: Regrets are associated with increased risks of sick leave, even in young healthcare professionals. Use of coping strategies partially mediated these associations in nurses. The results of this study should be used to inform interventions to reduce emotional burdens and enhance protective coping strategies.